Applicability of a change of direction ability field test in soccer assistant referees - Castagna, C.; Impellizzeri, F. M.; Bizzini, M.; Weston, M.; Manzi, V. (The Journal of Strength and Conditioning Research, 2011)
The aim of this study was to examine the applicability of a test for change of direction ability (10-8-8-10 test, involving line and sideward sprinting, 36 m) in elite-level soccer assistant referees (ARs). One hundred AR of the first-second and third Italian Championships (ARA-B and ARC, n = 50, respectively) performed the 10-8-8-10 on 3 separate occasions. Twenty AR authorities scored test relevance (1-5 scale, from trivial to very large) for logical validity using a questionnaire. Construct validity was examined comparing ARA-B and ARC for the 10-8-8-10 performance. Short-term reliability was assessed testing a random selection of ARs (n = 64) over 3 separate occasions every other day. Performance in the 10-8-8-10 test was assumed as total coverage time using telemetric photocells. Results showed that the 10-8-8-10 test was perceived as possessing from large (n = 4/20) to very-large (n = 16/20) relevance to AR physical match performance. No significant performance difference was found between competitive levels (p = 0.57). Area under the curve (= 0.49; p = 0.87) showed no significant sensitivity of 10-8-8-10 in detecting competitive-level difference. The intraclass correlation coefficient (n = 64) and typical error of measurement (test 2 vs. 3) values were 0.90 (p < 0.0001) and 0.18 seconds, respectively. This study showed that the 10-8-8-10 test possesses logical validity, good reliability, and it is independent of the competitive level. As such, this original investigation represents the first step in the identification and assessment of a valid and reliable AR change of direction test. Given the strength of our findings, governing bodies should look to integrate the 10-8-8-10 test into the fitness test protocols devised for ARs, with scores =9.67 being considered as a starting point for the empirical validation of minimum selection criteria for elite-level ARs.